2019
DOI: 10.17094/ataunivbd.390820
|View full text |Cite
|
Sign up to set email alerts
|

Bozdoğan’da (Falco columbarius) Plexus lumbosacralis’i Oluşturan Spinal Sinirlerin Makroanatomik Yapısı

Abstract: Öz: Sunulan araştırmada 5 adet ergin erkek doğan (Falco columbarius)'ın plexus lumbosacralis'ini oluşturan spinal sinirlerin stereomikroskop altında diseksiyonu yapılarak; sinirli liflerinin seyirleri ve innerve ettikleri bölgeler ortaya konmuştur. Plexus lumbosacralis'in synsacrum'un ventral'inde yer alan altı (2-7) adet synsacral spinal sinirin ramus ventralis'lerinden oluşturulduğu gözlendi. Plexus lumbalis'in os ilium'um cranioventral'inde 2.-4. spinal sinirlerin ventral dalları, plexus sacralis'in ise 4.-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In recent years, studies on dogs have been conducted on sperm cells (Yousef et al, 2022), vaccines (Esmaeili et al, 2021), intestinal parasites (Ola-Fadunsin et al, 2023), serum concentrations of hormones (Mosallanejad et al, 2021), and canine distemper virus (Mohtahedzade et al, 2023). In previous studies, it was observed that the plexus lumbosacralis was studied in species such as Van cat (Nur et al, 2021), fox (De Carvalho Barros et al, 2019), Baladi breed dog (El-Gendy et al, 2021), sparrowhawk (Balkaya & Ozudogru, 2016), merlin (Akalan et al, 2019), puma (Londoño-Osorio et al, 2020, and helmeted guineafowl (Nilgun & Ismail, 2021). However, no study has been done on plexus lumbosacralis in Aksaray Malaklı breed dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on dogs have been conducted on sperm cells (Yousef et al, 2022), vaccines (Esmaeili et al, 2021), intestinal parasites (Ola-Fadunsin et al, 2023), serum concentrations of hormones (Mosallanejad et al, 2021), and canine distemper virus (Mohtahedzade et al, 2023). In previous studies, it was observed that the plexus lumbosacralis was studied in species such as Van cat (Nur et al, 2021), fox (De Carvalho Barros et al, 2019), Baladi breed dog (El-Gendy et al, 2021), sparrowhawk (Balkaya & Ozudogru, 2016), merlin (Akalan et al, 2019), puma (Londoño-Osorio et al, 2020, and helmeted guineafowl (Nilgun & Ismail, 2021). However, no study has been done on plexus lumbosacralis in Aksaray Malaklı breed dogs.…”
Section: Introductionmentioning
confidence: 99%